2011
DOI: 10.1186/1743-0003-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of selected stimulation patterns on the perception threshold in electrocutaneous stimulation

Abstract: BackgroundConsistency is one of the most important concerns to convey stable artificially induced sensory feedback. However, the constancy of perceived sensations cannot be guaranteed, as the artificially evoked sensation is a function of the interaction of stimulation parameters. The hypothesis of this study is that the selected stimulation parameters in multi-electrode cutaneous stimulation have significant impacts on the perception threshold.MethodsThe investigated parameters included the stimulated locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…These findings are in accordance with a study that found significantly lower thresholds at 10 Hz compared to 75 Hz [3]. Nevertheless, another study [24] reported a sensory threshold inversely related to the frequency, a finding diverging from ours, although the sample assessed by the author was small. These results may be associated with a greater perception of painful stimuli in elderly subjects, since the frequency of 5 HZ excites the afferent fibers A‐δ and C, which convey low‐frequency stimuli, whereas afferent fibers A‐β convey higher frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in accordance with a study that found significantly lower thresholds at 10 Hz compared to 75 Hz [3]. Nevertheless, another study [24] reported a sensory threshold inversely related to the frequency, a finding diverging from ours, although the sample assessed by the author was small. These results may be associated with a greater perception of painful stimuli in elderly subjects, since the frequency of 5 HZ excites the afferent fibers A‐δ and C, which convey low‐frequency stimuli, whereas afferent fibers A‐β convey higher frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…A logarithmic relationship was found between the pulse number and the sensation magnitude. In the previous study on the effects of pulse number on PT, an inverse relationship was found between PT and the pulse number: PT = c + d/n [29]. This may imply that the PT is negatively related to the sensation magnitude in a nonlinear fashion.…”
Section: On Effects Of Pulse Number On Evoked Sensationsmentioning
confidence: 91%
“…Specifically, the shorter the phase duration, the greater the amplitude required to reach these thresholds (38,39). Our results showed that sensitivity increased in the premenstrual phase (P5) for all of the examined physical parameters.…”
Section: Discussionmentioning
confidence: 99%